Development of “Stafolding”: A Computer-Based Scaffolding Interactive Learning Media to Enhance Students’ Mathematical Problem-Solving Ability - Taulia Damayanti; Bertu Rianto Takaendengan; Djihad Wungguli; Karman Tambiyo; Elsa Ekaputri Utina (Jambura Journal of Mathematics Education, 2025)
The low level of students’ mathematical problem-solving ability remains a challenge in the learning process, particularly in statistics topics. One effective approach to address this issue is scaffolding, which provides temporary support that helps students understand problems and find solutions independently. However, in classroom settings, individualized scaffolding is often suboptimal due to the large number of students compared to the limited number of teachers and the relatively short instructional time. This study aims to develop a computer-based scaffolding interactive learning medium that is feasible and practical for enhancing students’ mathematical problem-solving ability. The research employed a Research and Development (RD) design using the ADDIE model, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The media were developed using Canva, Microsoft PowerPoint, and iSpring Suite, and published via GitHub Pages for online accessibility. The validation results showed a feasibility score of 91.11% from material experts and 93.33% from media experts, both categorized as excellent. The practicality tests conducted by teachers and students each obtained a score of 92%, indicating that the media are easy to use and effective in facilitating learning. Therefore, the interactive learning media “Stafolding” are considered feasible and practical to be used as a computer-based scaffolding tool in mathematics learning.